Regional disparities in knowledge-intensive sectors. A comparative study of Poland and Czechia in the context of sustainable development - Miszczak, Katarzyna; Mempel-Śnieżyk, Anna; Dědková, Jaroslava (Regionalne dysproporcje w sektorach wiedzochłonnych. Studium porównawcze Polski i Czech w kontekście zrównoważonego rozwoju, 2025)
The study aimed to explore regional disparities in the employment of high-technology and knowledge-intensive sectors across Polish and Czech regions from 2019 to 2023 to identify which areas are thriving in innovation and economic growth and which are lagging, highlighting regional imbalances. The research applied a quantitative approach, utilising publicly available data from Eurostat to explore trends in employment in knowledge-intensive sectors and R&D personnel. The study also incorporated visual representations to illustrate regional trends and disparities. High-technology and knowledge-intensive sectors are critical for future economic resilience. Exploring disparities can reveal how prepared different regions are for economic shifts such as the transition to Industry 4.0 and the green economy. This research contributes to the existing literature by offering a comparative, longitudinal analysis of regional disparities in knowledge-intensive sectors in Poland and Czechia. It highlights the implications of these disparities for sustainable development and regional innovation policies, offering a unique perspective on the socio-economic dynamics within Central and Eastern Europe.
Biblioteka Regionalisty = Regional Journal, 2025, Nr 25, s. 133-147
Keywords: knowledge-intensive services; high-technology manufacturing sectors; sustainable development; Poland; Czechia; usługi wiedzochłonne; sektory produkcji wysokich technologii; zrównoważony rozwój; Polska; Czechy